The development of a clinical portfolio as a learning approach for intensive care nurses in a private nursing education institution in Gauteng - Potgieter, Lizelle (My University, 2016)
Clinical portfolios guide clinical learning experiences and assess the student’s attainment of programme outcomes. The researcher perceived a need to redesign the portfolio of the Diploma in Critical Care Nursing (General) programme offered by a private nursing education institution in Gauteng. The researcher experienced that neither the student nor the educator utilised the clinical portfolio effectively in the development and transformation of the intensive care nursing student at the private nursing education institution. The purpose of the study was to improve the structure and enhance the use of clinical portfolios as a learning approach and as an assessment strategy in intensive care nursing education. The study objectives for the study was: Stage 1: to solicit the opinion of students and their educators on the quality of the existing clinical portfolio and their recommendations for the design and utilization of a revised clinical portfolio; Stage 2: to design a revised clinical portfolio for intensive care nursing students based on educator and student opinion and literature review; Stage 3: to solicit the opinion of nursing education experts on the revised clinical portfolio and to make changes as required. This study is a shortened intervention research with qualitative methods for data collection from intensive care nursing students, lecturers, clinical facilitators, and nursing education experts. A content analysis (Tesch, 1990) was used for data analysis. The setting for this study was set in a private nursing education institution in Gauteng that offers the intensive care programme. Purposive sampling was used to select participants of the three focus groups. Students were not as concerned about the structure of the clinical portfolio as they were concerned about how the portfolio assists them in reaching their outcomes. Small changes were recommended. Educators and the literature were more concerned about the structure of the clinical portfolio and less concerned about the process of application. The clinical portfolio was redesigned to improve its function as a learning approach and is ready for piloting in a larger sample group. Students have concrete ideas about how to deal with some of their frustrations working in the clinical field but do not really know how to structure a clinical portfolio. The educators were in a much better position to comment on the structure of the clinical portfolio and what must be considered to improve clinical learning. Different interview protocols should be used for students, educators and educator experts.
A Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Nursing. Johannesburg, 2016.
Keywords: Clinical Portfolio; Critical Care Nursing